2020
DOI: 10.1186/s12885-020-07219-z
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of the VICTORIA study: personalized vitamin D supplementation for reducing or preventing fatigue and enhancing quality of life of patients with colorectal tumor - randomized intervention trial

Abstract: Background: Cancer-related fatigue represents one major cause of reduced quality of life in cancer patients and can seriously affect the physical, emotional, and cognitive functioning impeding coping with the disease. Options for effective treatment of cancer-related fatigue are limited, consisting only of non-pharmacologic interventions like physical activity, psychosocial, and mind-body interventions. Recent evidence suggests that vitamin D 3 supplementation might alleviate cancer-related fatigue. However, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Two trials investigating the effect of vitamin D supplementation on fatigue in cancer patients are ongoing [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Two trials investigating the effect of vitamin D supplementation on fatigue in cancer patients are ongoing [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Testing and correction of 25(OH)D levels are commonly studied in cases of fatigue [7,[89][90][91][92][93], but more studies are needed to prove the effectiveness of vitamin D supplementation in reducing or preventing of the CRF. The VICTORIA study aims to confirm this association through a randomized controlled trial [94]. A recent genetic analysis between low 25(OH)D levels and fatigue showed little evidence of a causal effect, suggesting an unlikely protective effect of 25(OH)D on fatigue, but considering a lifelong exposure to a low serum concentration, unlike observational or intervention studies which investigate the association between short-term changes in 25(OH)D concentration and fatigue [95].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design, including the main and interim analyses, have been reported in the trial protocol [ 14 ]. VICTORIA is an ongoing parallel-group, randomized, double-blind, placebo-controlled clinical trial.…”
Section: Methodsmentioning
confidence: 99%
“…Eligible patients had a diagnosis of nonmetastatic colorectal cancer (not stage IV), a tumor surgery within the past year (type of surgery not specified), and vitamin D insufficiency (25(OH)D) levels < 50 nmol/L) at the time of screening. Most of the patients in the interim analysis were recruited before a protocol amendment made for the 25(OH)D level inclusion cut-off and needed even lower, season-standardized 25(OH)D levels < 50 nmol/L (see study protocols for details [ 14 ]). Exclusion criteria comprised mainly an already existing supplementation with high-dose vitamin D, high-dose calcium therapy, and medical conditions/concurrent medication contraindicated for vitamin D 3 therapy according to the Summary of Product Characteristics (see Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%